Mixed Transition Metal (Oxy)fluoride Paramagnet Chains: Synthesis, Structure, and Characterization. Issue 26 (10th July 2019) - Ahmed, Belal; Jo, Hongil; Yoon, Sung Won; Choi, Kwang‐Yong; Chen, Wei‐tin; Chou, Fangcheng; Ok, Kang Min
Abstract : Three mixed transition metal (oxy)fluorides, [Ni(pz)4 ][VO2 F3 ] (1 ), [Cu(pz)4 ][TiF6 ] (2 ), and [Cu(mpz)4 ][ZrF6 ] (3 ) (pz = pyrazole; mpz = 3‐methylpyrazole) were synthesized by combining asymmetric polyhedra of early transition metal cations, [VO2 F3 ] 2– /[TiF6 ] 2– /[ZrF6 ] 2– and basic building units (BBUs) of late transition metal cations, [Ni(pz)4 ] 2+ /[Cu(pz/mpz)4 ] 2+ via hydrothermal reactions. Compound 1 consists of chains with disordered F – and O 2–, whereas compounds 2 and 3 are composed of chains containing fully ordered F – and O 2– . The ordered structures for compounds 2 and 3 are achieved by providing the cationic contacts for [MF6 ] 2– (M = Ti, Zr) anions to [Cu(pz/mpz)4 ] 2+ cations and to pyrazole/3‐methylpyrazole ligands through covalent bonding and hydrogen bonding interactions, respectively. Detailed structural analysis suggests that the distinctive structure‐directing anionic groups ([VO2 F3 ] 2–, [TiF6 ] 2–, or [ZrF6 ] 2– ) and hydrogen bonding networks are responsible for the linear chain structures. The lower‐energy and higher‐energy absorption optical band gaps are generated from the d–d electronic transitions, and the octahedral distortions of M′ 2+ (M′ = Ni, Cu) cations for all the reported compounds. Both magnetic susceptibility and magnetization measurements of compounds 1, 2, and 3 show no Bonner–Fisher behavior expected for the linear spin chain. Rather, compounds 1, 2, and 3 behave like paramagnets without developing any magnetic order. Abstract : One‐dimensional linear chain oxyfluoride structures were built from the corner sharing of alternating trans ‐directing anionic polyhedra in trans ‐coordinating fashion, as well as both intra‐ and interchain hydrogen bonding networks.